Мотиви регуляторних послідовностей у промоторних ділянках гена MGMT людини в межах мобільних генетичних елементів - Підпала, О.В.; Лукаш, Л.Л. (Фактори експериментальної еволюції організмів, 2015)
Aims. It has been carried out analysis of the MGEs in promoters of human MGMT gene for the sequences homologous to binding sites of the transcription factors. Methods. Searching and identifying MGEs were realised by using CENSOR (http://www.girinst.org). The functional sites were defined by the program TFSEARCH: Searching Transcription Factor Binding Sites (ver 1.3) (http://www.cbrc.jp/research/db/TFSEARCH.html). Results. Two LTR repeats and the fragment of the DNA transposon were identified in promoter reference sequence of human MGMT gene. In addition to new potential cis-regulatory sequences one LTR repeat containing known hormone response element (GRE) and minimal promoter sequence and SP1 site were localized within the transposon DNA fragment. It has been shown that the AluJr repeat in known promoter has certain homology with seven binding sites for the transcription factors. Conclusions. The obtained results allow considering MGE identified in promoter of MGMT gene as a carrier for the potential cis-regulatory elements.